Kebijakan Pengendalian Persediaan Bahan Baku Kertas Menggunakan Model P Berdasarkan Peramalan Kebutuhan Produksi (Studi Kasus: Penerbit X) - Triska, Anita; Sani, Jihan Gita (Diophantine Journal of Mathematics and Its Applications, 2023)
Raw materials are important for a company, but the stockpile of raw materials that accumulates too many and too long adds to the inventory costs. Therefore, an appropriate inventory policy is needed to meet uncertain needs. This study discusses the uncertain need for paper raw materials at the Publisher X using the Additive Decomposition Forecasting method to determine the paper needs in the future. The Additive Decomposition Forecasting Method is used since the demand for paper raw materials is seasonal and tends to increase. Furthermore, after knowing the need of paper raw materials, inventory control planning is carried out by using P Model with the back order case because of the constant order period. The results of this study indicate that by implementing an inventory control policy with P Model with the case of back order, the Publisher X is able to save as 0.9067% of total inventory cost compared to the total cost using the company’s policy that have been used before.